Concurrent versus delayed feedback: biomechanics in rowing - George, W. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Biomechanical characteristics of rowers are often compared with `gold standard` characteristics in order to identify improvable aspects of technique and to facilitate technique improvements. Biomechanical characteristics of athletes from the Canadian Women`s Under 23 Rowing team (n=8) were evaluated and two different methods of feedback were trialed to assess their effectiveness. Results showed 1 of 6 biomechanical characteristics to change significantly (p <.05) between trials. However, since boat speed (m/s) increased by 18.2% when using concurrent augmented feedback instead of a combination of visual and verbal delayed feedback, concurrent feedback was adopted by the team. Literature suggests this method would require alteration to be successful in different sports and concurrent feedback should be supplemented by delayed feedback in order for long term skill retention to occur.